The effect of financial inclusion and economic integration on green growth in ASEAN - Anak Agung Ketut Agung Dharma Putra; Siskarossa Ika Oktora (Journal of Economics and Development, 2024)
Purpose – This study was conducted to review the overview of green growth and examine the role of financial inclusion as well as economic integration and other variables on green growth in Association of Southeast Asian Nations (ASEAN) countries. Design/methodology/approach – Principal component analysis (PCA) was used to construct financial inclusion variables and panel data regression analysis to examine the effect of financial inclusion and economic integration on green growth in 10 ASEAN countries from 2010 to 2021. Findings – The results showed that financial inclusion had played a role in supporting green growth in ASEAN. The rapid development of green finance and green bonds promoted the implementation of better green growth. The variables of export diversification and trade openness had a significant effect on green growth. Therefore, there is a need for appropriate policies to prevent negative effects on the environment and the behavior of ASEAN countries. Research limitations/implications – The findings of this study suggest that policymakers in ASEAN countries not only focus on gaining economic benefits from financial inclusion and economic integration activities but also pay attention to environmental impacts. Moreover, the ASEAN region is actively developing strategic steps in providing easy access to capital and finance as well as expanding international trade activities through ASEAN Free Trade Area (AFTA). Therefore, it is hoped that apart from being able to establish sustainable policies, this region will also encourage and optimize previous policies to make them more environmentally friendly. Originality/value – This study used a green growth approach with the Index by the Global Green Growth Institute. This index considered aspects of green economic opportunities and social inclusion that have not been applied in previous studies. In addition, this study contributed to review the activities of economic integration and financial inclusion and the sustainability of green growth in ASEAN countries. Until now, there has been no research focused on ASEAN; even though ASEAN has long carried out economic integration and encouraged financial inclusion policies, this region is vulnerable to environmental degradation issues.